Graphene-loaded nickel-cobalt diatomic catalyst, preparation method thereof and lithium air battery
By supporting the nickel-cobalt diatomic catalyst on the graphene matrix, the problems of single-atom catalyst sites and high cost of Ni-Ru catalysts are solved, and efficient, stable and economical improvement in electrochemical performance of lithium air batteries is achieved.
Patent Information
- Application Number
- CN202510381598.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, single-atom catalysts have problems with single catalytic sites and low metal loading, while Ni-Ru bimetallic catalysts have limited the economicality of their large-scale application due to the high cost of the noble metal ruthenium and the insufficient long-term stability and catalytic activity of the catalyst.
The graphene-supported nickel-cobalt diatom catalyst is prepared by hydrothermal-high-temperature thermal reduction method. The single-atom or atom-pair sites of nickel and cobalt are supported on the graphene matrix doped with nitrogen element to ensure uniform distribution and efficient utilization of the catalytic sites.
It improves the catalytic activity and long-term stability of the catalyst, reduces the cost of the catalyst, significantly improves the discharge capacity, rate performance and cycle stability of lithium air batteries, and is suitable for large-scale applications.
Smart Images

Figure CN119890554A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphene catalyst materials, and in particular to a graphene-supported nickel-cobalt diatomic catalyst and a preparation method thereof, and a lithium-air battery. Background Art
[0002] The rapid consumption of fossil energy has caused energy shortages and environmental pollution, making the development of renewable energy such as wind power and hydropower urgent. However, these energy sources cannot meet the portable energy requirements of society, so it is very important to develop green, environmentally friendly, stable and efficient energy storage and conversion devices. In this context, lithium-oxygen batteries are considered to be a new generation of energy storage devices with great application prospects because of their extremely high theoretical specific capacity comparable to gasoline and their environmental friendliness. As a unique semi-open system, the positive active material of lithium-oxygen batteries is air, and the battery uses the reversible formation and decomposition of lithium peroxide as the basic electrochemical reaction.
[0003] However, after decades of development, lithium-oxygen batteries still have some problems. The cathode is the core component of lithium-air batteries (LOBs), providing active sites for electrochemical reactions (i.e., Li2O2 formation: oxygen reduction reaction, ORR; and Li2O2 decomposition: oxygen evolution reaction, OER), which occur during discharge and charge processes, respectively. In addition, the cathode also plays an important role in accommodating the discharge products. However, LOBs cathodes show lower-than-expected capacity, while their cycle efficiency and rate performance are poor. In addition, in terms of lithium anode, performance degradation of lithium metal due to dendrite growth during repeated lithium dissolution and deposition cycles remains a key issue. At the same time, it is also crucial to prevent lithium from having harmful reactions with impurities such as electrolyte and moisture in the ambient air.
[0004] In order to solve the above problems, in terms of positive electrode, researchers are committed to exploring efficient electrocatalysts with better oxygen reduction / oxygen evolution reaction kinetics. The current achievements are mainly concentrated in carbon materials, precious metals, transition metal oxides, metal nitrides, metal sulfides and metal carbides. At the same time, various stabilization strategies have been proposed for negative electrodes, such as constructing a new replaceable lithium-containing negative electrode, applying electrolyte additives / modifications and constructing protective layers. Single-atom catalysts are widely studied due to their high atomic utilization and catalytic activity.
[0005] Chinese Patent 1 (Patent Publication No.: CN117638329A): discloses an atomically dispersed nickel-based catalyst and its preparation method and application. As a positive electrode catalytic material, it increases the contact area between the electrode and the electrolyte, improves the three-phase interface problem, and provides more sites for the accommodation of discharge products. However, single-atom catalysts themselves have certain limitations, including a single catalytic site and low metal loading, which limit their catalytic activity and versatility. At the same time, the instability of the negative electrode of the lithium-air battery will also affect the performance of the battery.
[0006] Chinese Patent 2 (Patent Publication No.: CN118352546A): discloses a Ni-Ru bimetallic catalyst and its preparation method and application, wherein the Ni-Ru bimetallic catalyst includes a substrate doped with nitrogen, nickel catalytic sites and ruthenium catalytic sites loaded on the surface of the substrate; the substrate is reduced graphene oxide; the nickel catalytic sites are loaded on the surface of the substrate in the form of single atoms and / or clusters, and the ruthenium catalytic sites are loaded on the surface of the substrate in the form of at least one of single atoms, clusters, and nanoparticles. It is used as a catalytic positive electrode material for lithium-oxygen batteries. Due to the presence of the synergistic catalytic effect of the Ni-Ru bimetallic catalyst, it can significantly reduce the charge overpotential, increase the discharge capacity, and improve the cycle life of the battery. However, although this catalyst performs well in some applications, there are still some problems: ruthenium is a precious metal with a high price, which limits the economic feasibility of its large-scale application; in addition, under certain reaction conditions, the long-term stability and catalytic activity of the Ni-Ru catalyst still have room for improvement.
[0007] Therefore, the existing technology needs to be improved. Summary of the invention
[0008] In the prior art, single-atom catalysts have the disadvantages of a single catalytic site and low metal loading, while Ni-Ru bimetallic catalysts are expensive, limiting the economic feasibility of their large-scale application. Therefore, the present invention provides a graphene-loaded nickel-cobalt diatomic catalyst and a preparation method thereof, and a lithium-air battery for solving the above problems.
[0009] To achieve the above object, in a first aspect, the present invention provides a method for preparing a graphene-supported nickel-cobalt diatomic catalyst, which comprises the following specific steps: S1, mixing nickel salt and cobalt salt with water respectively, and mixing according to the volume ratio of nickel salt solution to cobalt salt solution of 1: (1-4) to obtain a mixed salt solution; S2, adding the mixed salt solution and deionized water to the graphene oxide aqueous solution treated with ultrasound, stirring and mixing to obtain a precursor solution, wherein the volume ratio of the total volume of the mixed salt solution and deionized water to the graphene oxide aqueous solution is 3: (3-5); S3, transferring the precursor solution to a hydrothermal reaction kettle, performing a hydrothermal reaction, and obtaining a precursor gel; S4, freeze-drying the precursor gel; S5. Thermally reduce the freeze-dried precursor in an ammonia atmosphere to obtain a nitrogen-doped graphene-supported nickel-cobalt diatomic catalyst.
[0010] In one implementation, in S1, the nickel salt includes any one or more of NiCl2·6H2O, Ni(NO3)2·6H2O and Ni(CH3COO)2·4H2O; the cobalt salt includes any one or more of CoCl2·6H2O, CoCl2·H2O and Co(NO3)2.
[0011] In one implementation, in S1, the concentration of the nickel salt solution is 0.8 mg / l-1.2 mg / ml; the concentration of the cobalt salt solution is 0.8 mg / l-1.2 mg / ml.
[0012] In one implementation, in S2, specifically including: pre-ultrasonicating the graphene oxide aqueous solution for 2 to 5 hours, wherein the concentration of the graphene oxide aqueous solution is 1.5 to 2.5 mg / ml, magnetically stirring the nickel salt solution, the cobalt salt solution and the pre-ultrasonicated graphene oxide aqueous solution for 0.5 hours, and then ultrasonicating for 0.5 hours to obtain a precursor solution.
[0013] In one implementation, in S3, specifically including: moving the precursor solution into a hydrothermal reactor, sealing it and placing it in a forced air drying oven for hydrothermal reaction, the hydrothermal reaction temperature is 170-190°C, the hydrothermal reaction time is 5-7h, and a black precursor gel with a regular cylindrical appearance is obtained, and then the precursor gel is soaked and cleaned three times with deionized water, each soaking time is 30 minutes.
[0014] In one implementation, in S4, specifically includes: placing the cleaned precursor gel into a refrigerator for freezing, the freezing temperature is -5°C, and the freezing time is 10 to 15 hours; and then placing it into a vacuum dryer for drying, and the drying time is 60 to 72 hours.
[0015] In one implementation, in S5, the thermal reduction is carried out in a mixed atmosphere of inert gas and ammonia; the thermal reduction temperature is 850°C~950°C, the heating rate of the thermal reduction is 4°C / min~6°C / min, and the thermal reduction time is 1h~2h; the gas flow rate of the mixed atmosphere is 100ml / min.
[0016] In one implementation, in S5, the mass percentage of nitrogen element doped in the graphene-supported nickel-cobalt diatomic catalyst after thermal reduction is 1.7wt%~3.1wt%, the nickel active sites and the cobalt active sites are supported on the surface of the graphene matrix in the form of single atoms or Ni / Co atomic pairs, and the total mass of the cobalt catalytic sites is 0.0211wt%~0.1472wt% of the mass of the graphene-supported nickel-cobalt diatomic catalyst.
[0017] In a second aspect, the present invention further provides a graphene-supported nickel-cobalt diatomic catalyst, which is prepared by any of the above-mentioned methods for preparing the graphene-supported nickel-cobalt diatomic catalyst.
[0018] In a third aspect, the present invention further provides a lithium-ion air battery, which comprises the above-mentioned graphene-supported nickel-cobalt diatomic catalyst.
[0019] Beneficial effects: The present invention improves the catalytic activity and long-term stability of the catalyst through the synergistic effect of the nitrogen-doped graphene matrix and the nickel-cobalt diatomic catalytic sites during the thermal reduction process; during the preparation process, the combination of freeze-drying and thermal reduction avoids the agglomeration of the precursor at high temperature, ensuring the uniform distribution and efficient utilization of the catalytic sites. The use of cobalt in the present invention significantly reduces the cost of the catalyst, improves the economy, and is suitable for large-scale application. The present invention provides a graphene-supported nickel-cobalt diatomic catalyst with high-efficiency catalytic performance, stability and broad application prospects, and exhibits excellent electrochemical performance in lithium-ion air batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a flow chart of the steps of the method for preparing the graphene-supported nickel-cobalt diatomic catalyst provided by the present invention; Figure 2 Schematic diagram of the process flow of the preparation method of the graphene-supported nickel-cobalt diatomic catalyst of Examples 1 to 3; Figure 3 Spherical aberration transmission electron microscopy images of the graphene-supported nickel-cobalt diatomic catalysts prepared in Examples 1 to 4; Figure 4 X-ray photoelectron spectra of the NiCo2-N / rGO diatomic catalyst prepared in Example 2 and the Co single atom catalyst prepared in Comparative Example 1; Figure 5 This is a Fourier transform extended X-ray absorption fine structure image of the NiCo2-N / rGO diatomic catalyst prepared in Example 2; Figure 6 The first cycle discharge capacity curve of the lithium-air battery with the catalytic positive electrode prepared by the catalysts prepared in Examples 1 to 3 and Comparative Example 1; Figure 7The charge and discharge performance curves of lithium-air batteries using the catalysts prepared in Example 2 and Comparative Example 1 to prepare catalytic positive electrodes; Figure 8 The rate performance curve of the lithium-air battery using the catalyst prepared in Example 2 and Comparative Example 1 to prepare the catalytic positive electrode; Fig. 9 The cycle stability curve of the lithium-air battery using the catalyst prepared in Examples 1 to 3 and Comparative Example 1 to prepare the catalytic positive electrode; Fig.10 The limiting current density curve of the lithium symmetric battery with the composite lithium metal negative electrode of Example 2; Fig.11 This is a cycle stability curve of the lithium-air battery with a double-atom catalyst catalytic positive electrode and a composite lithium metal negative electrode prepared in Example 2.
[0021] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0023] Please refer to Figure 1 , Figure 1 The present invention provides a method for preparing a graphene-supported nickel-cobalt diatomic catalyst, which comprises the following specific steps: S1, mixing nickel salt and cobalt salt with water respectively, and mixing according to the volume ratio of nickel salt solution to cobalt salt solution of 1: (1-4) to obtain a mixed salt solution; S2, adding the mixed salt solution and deionized water to the graphene oxide aqueous solution treated with ultrasound, stirring and mixing to obtain a precursor solution, wherein the volume ratio of the total volume of the mixed salt solution and deionized water to the graphene oxide aqueous solution is 3: (3-5); S3, transferring the precursor solution to a hydrothermal reaction kettle, performing a hydrothermal reaction, and obtaining a precursor gel; S4, freeze-drying the precursor gel; S5. Thermally reduce the freeze-dried precursor in an ammonia atmosphere to obtain a nitrogen-doped graphene-supported nickel-cobalt diatomic catalyst.
[0024] Specifically, in S1, the nickel salt includes any one or more of NiCl2·6H2O, Ni(NO3)2·6H2O and Ni(CH3COO)2·4H2O; the cobalt salt includes any one or more of CoCl2·6H2O, CoCl2·H2O and Co(NO3)2. The nickel salt and cobalt salt have good water solubility. When mixed with the graphene oxide aqueous solution that has been pre-ultrasonic dispersed, a precursor solution with uniform solute distribution can be formed, so that the solution structure is conducive to the effective loading of nickel and cobalt elements on the surface of graphene oxide. Furthermore, the concentration of the nickel salt solution is 0.8mg / l~1.2mg / ml; the concentration of the cobalt salt solution is 0.8mg / l-1.2mg / ml.
[0025] Specifically, in S2, it specifically includes: pre-ultrasonicating the graphene oxide aqueous solution for 2 to 5 hours, wherein the concentration of the graphene oxide aqueous solution is 1.5 to 2.5 mg / ml, and magnetically stirring the nickel salt solution, the cobalt salt solution and the pre-ultrasonicated graphene oxide aqueous solution for 0.5 hours, and then ultrasonicating for 0.5 hours to obtain a precursor solution.
[0026] Specifically, in S3, it specifically includes: moving the precursor solution into a hydrothermal reactor, sealing it and placing it in a blast drying oven for hydrothermal reaction, the hydrothermal reaction temperature is 170~190℃, the hydrothermal reaction time is 5~7h, and a black precursor gel with a regular cylindrical appearance is obtained, and then the precursor gel is soaked and cleaned three times with deionized water, each soaking time is 30min. Preferably, the hydrothermal reaction temperature is 180℃, and the hydrothermal reaction time is 6h. In this application, nickel-cobalt single atom sites and nickel-cobalt atom pairs are introduced into the hydrothermal reaction to produce a synergistic effect, so that the final product has excellent electrocatalytic performance and improves the rate performance of the lithium-air battery.
[0027] Specifically, in S4, the steps include: placing the cleaned precursor gel in a refrigerator for freezing, wherein the freezing temperature is -5°C and the freezing time is 10 to 15 hours; and then placing the precursor gel in a vacuum dryer for drying, wherein the drying time is 60 to 72 hours. Preferably, the freezing time is 12 hours and the drying time is 72 hours.
[0028] Specifically, in S5, the thermal reduction is carried out in a mixed atmosphere of inert gas and ammonia; the thermal reduction temperature is 850°C to 950°C, the heating rate of the thermal reduction is 4°C / min to 6°C / min, and the thermal reduction time is 1h to 2h; the gas flow rate of the mixed atmosphere is 100ml / min. Preferably, the temperature of the thermal reduction is 900°C, and the heating rate of the thermal reduction is 5°C / min. In the present application, nitrogen is doped by high-temperature thermal reduction, the electronic structure of the graphene carbon material is regulated, and the active center of the catalyst is increased, thereby improving the discharge capacity during the discharge process of the lithium-air battery.
[0029] Specifically, in S5, the mass percentage of nitrogen doped in the thermally reduced graphene-supported nickel-cobalt diatomic catalyst is 1.7wt%~3.1wt%, the nickel active sites and cobalt active sites are supported on the surface of the graphene matrix in the form of single atoms or Ni / Co atomic pairs, and the total mass of the cobalt catalytic sites is 0.0211wt%~0.1472wt% of the mass of the graphene-supported nickel-cobalt diatomic catalyst. The graphene-supported nickel-cobalt diatomic catalyst provided in the present application is added dropwise to the surface of the lithium negative electrode to prepare a composite lithium metal negative electrode, and the diatomic sites effectively regulate the uniform deposition of lithium, so that the lithium-air battery can operate stably at high rates.
[0030] The present invention is further described in detail below with reference to embodiments.
[0031] Embodiment 1 to Embodiment 3 In Examples 1 to 3, a graphene-supported nickel-cobalt diatomic catalyst is provided, such as Figure 2 As shown, the specific steps are as follows: S1: Dissolve 50 mg NiCl2·6H2O and 50 mg CoCl2·6H2O in 50 mL deionized water respectively, and stir magnetically for 0.5 h until completely dissolved to obtain nickel salt and cobalt salt solutions; S2: According to Table 1, a certain amount of the above nickel salt solution, cobalt salt solution and deionized water were added in a certain proportion to 50 mL of graphene oxide aqueous solution (2 mg / mL) that had been ultrasonically treated for 3 h, and then magnetically stirred for 0.5 h and ultrasonicated for 0.5 h to obtain four uniform and stable precursor solutions; S3: The four precursor solutions were transferred to the hydrothermal reactors respectively, sealed and placed in a forced air drying oven, and hydrothermally reacted at 180°C for 6 hours to obtain black cylindrical regular gel samples. The samples were soaked and washed with deionized water for three times, each time for 30 minutes; S4: The cleaned black gel sample was placed in a refrigerator for 12 h, and then placed in a vacuum dryer for 72 h to remove moisture. The sample was then transferred to a tube furnace for high temperature annealing at 5 °C min in an atmosphere of Ar (150 sccm) / NH3 (50 sccm) mixed gas. -1 The temperature was raised to 900°C at a heating rate and calcined at high temperature for 1 hour. The gas flow rate of the mixed gas was 100 ml min -1 , cooled to room temperature, and obtained the NiCo1-N / rGO catalyst of Example 1, the NiCo2-N / rGO catalyst of Example 2, and the NiCo3-N / rGO catalyst of Example 3, respectively.
[0032] Comparative Example 1 The difference of this comparative example is that no nickel salt solution is added to S2 and the amount of deionized water added is different, see Table 1, and the rest is the same as Example 2 to obtain Co-N / rGO.
[0033] Table 1. Specific data of raw materials added to each group See also Figure 3 , Figure 3 The spherical aberration transmission electron micrographs of the graphene-supported nickel-cobalt diatomic catalysts prepared in Examples 1 to 4, wherein a is the spherical aberration transmission electron micrograph of the graphene-supported cobalt single-atom catalyst Co-N / rGO prepared in Comparative Example 1, from which it can be seen that the cobalt element is distributed in the carbon matrix in the form of single atoms. b is the spherical aberration transmission electron micrograph of the graphene-supported nickel-cobalt diatomic catalyst NiCo2-N / rGO prepared in Example 2, from which it can be seen that after the addition of nickel element, in addition to single atoms, there are also atomic pairs, proving the successful synthesis of the diatomic catalyst.
[0034] See also Figure 4 , Figure 4 The X-ray photoelectron spectra of the NiCo2-N / rGO diatomic catalyst prepared in Example 2 and the Co single atom catalyst prepared in Comparative Example 1 are shown in Figure 2. Since the electronic structure of the material directly affects the catalytic performance of the material, X-ray photoelectron spectroscopy (XPS) was used to characterize the surface elemental composition and chemical state of Example 2 and Comparative Example 1. Figure 4 As shown, it can be found that the peak center of pyridine-N in NiCo2-N / rGO is shifted upward by about 0.1 eV compared with Co-rGO, proving that the added metal Ni element affects the coordination environment of Co, improves the catalytic activity of the material, and enhances the performance of lithium-air batteries.
[0035] See also Figure 5 , Figure 5The Fourier transform extended X-ray absorption fine structure image of the NiCo2-N / rGO diatomic catalyst prepared in Example 2 is shown in FIG. Figure 5 It can be seen that both the diatomic catalyst and the single-atom catalyst have two types of coordination, Co-N1 and Co-N2, which indicates that the cobalt element exists in the form of a single atom, and the Co-N2 bond strength of NiCo2-N / rGO is greater and the bond length is shorter, proving that Ni and Co interact with each other to produce a diatomic synergistic catalytic effect.
[0036] The graphene-supported nickel-cobalt diatomic catalysts prepared in Examples 1 to 3 and the graphene-supported cobalt single-atom catalyst prepared in Comparative Example 1 were used as catalytic positive electrode materials to prepare a lithium-air battery, and the specific steps were as follows: 1) Preparation of positive electrode plate of lithium-air battery: independently disperse the graphene-supported nickel-cobalt diatomic catalyst prepared in Examples 1 to 3 and the graphene-supported cobalt single-atom catalyst prepared in Comparative Example 1 in an isopropanol solution with a conductive agent Ketjen black and a 6% polytetrafluoroethylene binder in a mass ratio of 6:3:1, wherein the mass ratio of the Ni-Co bimetallic catalyst or the Co single metal catalyst to Ketjen black and to isopropanol is 1:120, and magnetic stirring is performed for 0.5 h and ultrasonication is performed for 3 h to obtain a uniform slurry; 50 μL of the above slurry is evenly applied on a carbon paper substrate, and vacuum dried at 90 ° C for 12 h to obtain a positive electrode plate, and the active material loading (catalyst + KB) of each positive electrode plate is 0.3 mg / cm 2 .
[0037] 2) Assembly and testing of lithium-air batteries: Assemble the obtained positive electrode sheets in a glove box filled with high-purity argon gas, with H2O and O2 contents less than 0.1ppm. Use metallic lithium (purity>99.9%) as the negative electrode, glass fiber film (GF / D) as the diaphragm, and a solution of lithium bis(trifluoromethanesulfonyl)imide dissolved in tetraethylene glycol dimethyl ether as the electrolyte (concentration of 1mol / L). The amount of electrolyte is 230μL, and CR2032 button batteries are assembled. Transfer the assembled battery to a lithium-oxygen battery test box, let it stand at room temperature for 3h, then introduce 1 atmosphere of oxygen, then let it stand in an oxygen atmosphere for 6h, and then introduce oxygen for the second time. The electrochemical performance of the lithium-air battery after the above treatment is tested. The test equipment is the Land battery test system (5V, 1mA), and the test voltage range is 2.0-4.5 / 5.0V.
[0038] The first cycle discharge capacity curve of the battery at a current density of 200 mA / g is as follows: Figure 6 As shown by Figure 6It can be seen that the first cycle discharge capacity of the lithium-air battery using the diatomic catalysts prepared in Examples 1-2 and the single-atom catalyst prepared in Comparative Example 1 to prepare the catalytic positive electrode is 22359, 24200, 13080 and 14959 mAh / g respectively.
[0039] The charge and discharge performance curve of the battery at a limited capacity of 1000mAh / g and a current density of 100mA / g is as follows: Figure 7 As shown by Figure 7 It can be seen that the overpotential of the lithium-air battery using the double-atom catalyst prepared in Example 2 to prepare the catalytic positive electrode is only 0.83V, while the overpotential of the lithium-air battery using the single-atom catalyst prepared in Comparative Example 1 to prepare the catalytic positive electrode is 1.38V.
[0040] The rate performance curves of the battery at a limited capacity of 1000mAh / g and different current densities are as follows: Figure 8 As shown by Figure 8 It can be seen that the lithium-air battery using NiCo2-N / rGO in Example 2 to prepare the catalytic positive electrode has almost no change in the discharge platform as the current density gradually increases (100mA / g~400mA / g), and the charging platform increases slowly and orderly. When the current density reaches 500mA / g~800mA / g, the battery discharge platform gradually decreases, and the charging platform still increases slowly and orderly. The battery is in a normal and stable operating state, but when the current density increases to 900mA / g, the battery discharge platform is at about 2V, indicating that the actual operation effect of the battery is poor under this parameter, exceeding the maximum tolerance. When the current decreases again, the battery charge and discharge platforms are restored to their original size, proving that the lithium-air battery using NiCo2-N / rGO in Example 2 to prepare the catalytic positive electrode has excellent rate performance. At the same time, for comparison, the rate performance of the Co-N / rGO (Comparative Example 1) electrode was also tested under the same conditions. The results showed that when the current density increased to 500mA / g, the battery discharge platform began to decline significantly, the discharge voltage was lower than 2V, and the battery decayed significantly. At a current density of 600mA / g~900mA / g, the battery could not operate normally.
[0041] The cycle stability curve of the battery at a limited capacity of 1000mAh / g and a current density of 200mA / g is as follows Fig. 9 As shown by Fig. 9 It can be seen that the lithium-air batteries with catalytic positive electrodes prepared using the catalysts of Examples 1-3 and Comparative Example 1 can stably cycle 27, 100, 63 and 40 times.
[0042] The NiCo2-N / rGO diatomic catalyst prepared in Example 2 is used as a negative electrode material in a lithium-air battery, and the specific steps are as follows: 1) Preparation of composite lithium metal negative electrode for lithium-air battery: The graphene-loaded nickel-cobalt diatomic catalyst prepared in Example 2 and the conductive agent Ketjen black are uniformly dispersed in tetraethylene glycol dimethyl ether at a mass ratio of 2:1, wherein the mass ratio of the Ni-Co diatomic catalyst to Ketjen black and to tetraethylene glycol dimethyl ether is 1:120, and magnetic stirring is performed for 0.5 h and ultrasonication is performed for 3 h to obtain a uniform mixed solution; 70 μL of the above mixed solution is evenly applied on the surface of the lithium sheet in a glove box filled with high-purity argon gas, and dried at 60°C for 12 h to obtain a composite lithium metal with a protective layer.
[0043] 2) Lithium-air battery assembly and testing: The obtained composite lithium metal was assembled in a glove box filled with high-purity argon gas with H2O and O2 contents less than 0.1ppm to assemble Li|Li and Li@NiCo2-N / rGO|Li@NiCo2-N / rGO symmetrical batteries.
[0044] In terms of limiting current density, as the current density increases from 0.1 mA cm ‒2 Gradually increase to 2.0 mA cm ‒2 , the overpotential of Li@NiCo2-N / rGO is lower than that of pure Li, indicating that the Ni / Co atomic sites can effectively regulate the lithium deposition / stripping behavior ( Fig.10 ). The composite lithium metal anode is used in lithium-air batteries. Fig.11 In the fourth cycle of the activation process of the Li-O2 battery with pure lithium metal anode, that is, at the limited capacity of 1000mAh / g and the current of 800mA / g, the battery cut-off voltage dropped below 2V. The Li@NiCo2-N / rGO composite anode can stably cycle for more than 70 cycles at a high current density of 1000 mA / g and a high capacity of 1000mAh / g, which significantly improves the electrochemical performance of the battery. Li@NiCo2-N / rGO has certain feasibility as a lithium metal anode.
[0045] In summary, the graphene-supported nickel-cobalt diatomic catalyst provided by the present invention comprises a reduced graphene oxide matrix doped with nitrogen, and nickel active sites and cobalt active sites loaded on the surface of the matrix; the nickel active sites and cobalt active sites are loaded on the surface of the matrix in the form of single atoms or Ni / Co atomic pairs. The present invention adopts a hydrothermal-high-temperature thermal reduction method to prepare a graphene-supported nickel-cobalt diatomic catalyst (NiCo-N / rGO), which uses reduced graphene oxide as a matrix, doping nitrogen elements to increase catalytic sites, and loads atomic-level nickel active sites and cobalt active sites thereon, and the sites are uniformly distributed in the carbon matrix in the form of single atoms or atomic pairs. Compared with single-atom catalysts, the present application provides the introduction of nickel and cobalt diatomic catalytic sites, adds more active centers, increases the metal loading, and improves the catalytic performance through synergistic effects. It is used as a catalytic cathode material for lithium-air batteries, showing excellent ORR / OER catalytic activity, which can effectively reduce the overpotential (0.83V), increase the discharge capacity (>24000mAh / g), improve the rate performance, and enhance the cycle stability of the battery (>100 cycles). In addition, this catalyst is added dropwise to the lithium sheet negative electrode to prepare a composite lithium metal negative electrode, so that the lithium-air battery can operate stably under high rate conditions (>70 cycles). In addition, compared with the ruthenium catalytic sites in the Ni-Ru bimetallic catalyst loaded on the substrate surface in the form of single atoms, clusters, and nanoparticles, the nickel active sites and cobalt active sites in the present application are loaded on the substrate surface in the form of single atoms or Ni / Co atomic pairs, and the nickel and cobalt in the form of single atoms or atomic pairs can maximize the utilization of active sites on the graphene surface, significantly improving the efficiency of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), while the cost of nickel and cobalt is relatively low, making the graphene-loaded nickel-cobalt diatomic catalyst provided by the present invention more economical in large-scale applications.
[0046] In summary, the graphene-supported nickel-cobalt diatomic catalyst provided by the present invention has a larger specific surface area and a higher pore volume. The higher specific surface area can promote the infiltration of the electrolyte, increase the three-phase reaction boundary, promote electron transfer and ion dissolution in the electrolyte, and improve the charge and discharge performance of the battery; in addition, the larger pore volume can also promote the positive electrode to accommodate more discharge products, increase the capacity of the battery, etc. In addition, in the graphene-supported nickel-cobalt diatomic catalyst, the coordination environment of the Co element is regulated by the Ni element, and paired metal sites are provided. The atomic-level Ni active sites and Co active sites are synergistically catalytic, which improves the catalytic activity and long-term stability of the catalyst, thereby realizing a lithium-air battery with better performance. The present invention avoids the agglomeration of the precursor at high temperature by combining freeze drying and thermal reduction, ensuring the uniform distribution and efficient utilization of the catalytic sites. Compared with the graphene-supported nickel-ruthenium diatomic catalyst, the present invention uses cobalt instead of ruthenium, which significantly reduces the cost of the catalyst, improves the economy, and is suitable for large-scale applications. In general, the present application provides an improved graphene-supported nickel-cobalt diatomic catalyst and a preparation method thereof, which overcomes the deficiencies in the prior art and has significant economic and performance advantages.
[0047] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a graphene-supported nickel-cobalt diatomic catalyst, characterized in that: The specific steps include: S1, mixing nickel salt and cobalt salt with water respectively, and mixing according to the volume ratio of nickel salt solution to cobalt salt solution of 1: (1-4) to obtain a mixed salt solution; S2, adding the mixed salt solution and deionized water to the graphene oxide aqueous solution treated with ultrasound, stirring and mixing to obtain a precursor solution, wherein the volume ratio of the total volume of the mixed salt solution and deionized water to the graphene oxide aqueous solution is 3: (3-5); S3, transferring the precursor solution to a hydrothermal reaction kettle, performing a hydrothermal reaction, and obtaining a precursor gel; S4, freeze-drying the precursor gel; S5. Thermally reduce the freeze-dried precursor in an ammonia atmosphere to obtain a nitrogen-doped graphene-supported nickel-cobalt diatomic catalyst.
2. The method for preparing the graphene-supported nickel-cobalt diatomic catalyst according to claim 1, characterized in that: In S1, the nickel salt includes any one or more of NiCl2·6H2O, Ni(NO3)2·6H2O and Ni(CH3COO)2·4H2O; the cobalt salt includes any one or more of CoCl2·6H2O, CoCl2·H2O and Co(NO3)2.
3. The method for preparing the graphene-supported nickel-cobalt diatomic catalyst according to claim 1, characterized in that: In S1, the concentration of the nickel salt solution is 0.8 mg / l-1.2 mg / ml; the concentration of the cobalt salt solution is 0.8 mg / l-1.2 mg / ml.
4. The method for preparing the graphene-supported nickel-cobalt diatomic catalyst according to claim 1, characterized in that: In S2, it specifically includes: pre-ultrasonicating the graphene oxide aqueous solution for 2-5 hours, wherein the concentration of the graphene oxide aqueous solution is 1.5-2.5 mg / ml, magnetically stirring the nickel salt solution, the cobalt salt solution and the pre-ultrasonicated graphene oxide aqueous solution for 0.5 hours, and then ultrasonicating for 0.5 hours to obtain a precursor solution.
5. The method for preparing the graphene-supported nickel-cobalt diatomic catalyst according to claim 1, characterized in that: In S3, it specifically includes: moving the precursor solution into a hydrothermal reactor, sealing it and placing it in a forced air drying oven for hydrothermal reaction, the hydrothermal reaction temperature is 170-190°C, the hydrothermal reaction time is 5-7h, and a black precursor gel with a regular cylindrical appearance is obtained, and then the precursor gel is soaked and cleaned three times with deionized water, each soaking time is 30 minutes.
6. The method for preparing the graphene-supported nickel-cobalt diatomic catalyst according to claim 1, characterized in that: In S4, it specifically includes: putting the cleaned precursor gel into a refrigerator for freezing, the freezing temperature is -5°C, and the freezing time is 10-15 hours; and then putting it into a vacuum dryer for drying, and the drying time is 60-72 hours.
7. The method for preparing the graphene-supported nickel-cobalt diatomic catalyst according to claim 1, characterized in that: In S5, the thermal reduction is carried out in a mixed atmosphere of inert gas and ammonia; the thermal reduction temperature is 850°C~950°C, the heating rate of the thermal reduction is 4°C / min~6°C / min, the thermal reduction time is 1h~2h; the gas flow rate of the mixed atmosphere is 100ml / min.
8. The method for preparing the graphene-supported nickel-cobalt diatomic catalyst according to claim 1, characterized in that: In S5, the mass percentage of nitrogen element doped in the thermally reduced graphene-supported nickel-cobalt diatomic catalyst is 1.7wt%~3.1wt%, the nickel active sites and the cobalt active sites are supported on the surface of the graphene matrix in the form of single atoms or Ni / Co atomic pairs, and the total mass of the cobalt catalytic sites is 0.0211wt%~0.1472wt% of the mass of the graphene-supported nickel-cobalt diatomic catalyst.
9. A graphene-supported nickel-cobalt diatomic catalyst, characterized in that: The method is prepared by the method for preparing the graphene-supported nickel-cobalt diatomic catalyst according to any one of claims 1 to 8.
10. A lithium-ion air battery, characterized in that: It includes the graphene-supported nickel-cobalt diatomic catalyst as described in claim 9.
Citation Information
Patent Citations
Ni-Ru bimetallic catalyst and preparation method and application thereof
CN118352546A
Carbon supported transition metal atom pair electrocatalyst and preparation method and application thereof
CN109686988A
Carbon-supported bimetallic monoatomic electrocatalyst, preparation method thereof, and application thereof
CN110247061A
Ni-Fe diatomic electrocatalyst, and preparation method and application thereof
CN111185176A
Atomic-scale dispersion nickel-based catalyst as well as preparation method and application thereof
CN117638329A
Cited By
Preparation method of ketoisoleucine sodium
CN121248401A